Citra Perempuan Sunda pada Tari Karawitan Istri - Cantika, Anindyajati; Narawati, Tati; Badaruddin , Saian (Universitas Negeri Medan, 2025)
This study aims to describe the image of Sundanese women as portrayed in the Tari Karawitan Istri (Women’s Karawitan Dance), a choreographic work by R. Sambas Wirakoesoemah in 1925. Tari Karawitan Istri is one of the classical Sundanese dances that has survived to this day, serving as a reflection of cultural values and the image of Sundanese women in its time. A qualitative research paradigm was employed using an ethnokoreological approach, applying stages such as dance structuralization, description, categorization, analysis, textual and contextual synthesis, and interpretation. Data were collected through observation, interviews, literature review, and documentation studies. Data analysis was conducted using triangulation to obtain a more accurate understanding of the dance. Textual findings reveal that the choreography of Tari Karawitan Istri consists of sixteen basic movement patterns, two locomotion movements, sixteen pure movements, and three gestures. The movements are characterized by lightness, slowness, and precision, which signify calmness, carefulness, and self control qualities that reflect the ideal character of Sundanese women as gentle and civilized figures. Contextually, this dance illustrates the image of Sundanese women during that era, who embodied refined behavior and upheld politeness as a core cultural value. The dance affirms that Sundanese women are not weak figures, but rather play a central role as educators and preservers of cultural values for future generations.